Persepsi Petani Terhadap Sistem Penanaman Jajar Legowo di Tempek Deman Subak Penatahan Desa Penatahan Kecamatan Penebel Kabupaten Tabanan - CAHYAGAMA, BINTANG FAJAR PATMA; PARINING, NYOMAN; PUTRA, I GEDE SETIAWAN ADI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2022)
Farmers' Perceptions on Jajar Legowo System in Tempek Deman,  Subak Penatahan, Penatahan Village, Penebel District, Tabanan Regency.  Jajar Legowo is one of the planting systems that were introduced by the Agricultural Development Agency to increase rice production. This study aims to determine the perceptions and expectations of farmers on the application of the Jajar Legowo system in rice cultivation in Tempek Deman, Subak Penatahan, Penatahan Village, Penebel District, Tabanan Regency. Data were collected through interviews, observation, and documentation toward 33 respondent farmers from February to July 2020. The results show that farmers' perception on the Jajar Legowo system is in the very good category. From the technical aspect, farmers hope that the Jajar Legowo system could be more simplified. From the economic aspect, farmers hope the Jajar Legowo system could improve labor efficiency and increase production yields. From the socio-cultural aspect, farmers hope that the Jajar Legowo system could improve cooperation so that farmers do not depend on planters. Farmers are expected to learn the planting technique together so that they get optimal results. The Department of Agriculture at Tempek Deman, Subak Penatahan should provide more assistance to farmers in planting so that they can plant according to the technical guidelines of the Jajar Legowo system and get optimal results.